A 24-h restraint with food and water deprivation: a potential method to establish a model of depression in pigs - Yang, Sen; Zheng, Qiang; Yin, Guoan (Frontiers in Veterinary Science, 2023)
Adverse stress, such as the long-term restriction of food intake and activity in intensive production, leads to a depression-like mental state in sows. Mood disorder, such as depression, is a widely concerned animal welfare issue. However, little is known about the biological mechanisms that underlie mood disorders in pigs. This study is the first attempt to establish a pig depression model by acute stress. A total of 16 adult Bama pigs were divided into control and model groups, with eight pigs (half male and half female) per group. The pigs in the model group were restrained for 24 hours in a dark and ventilated environment, with food and water deprived. After the restraint, behavioral tests (feed intake, sucrose preference test, open field test, novel object test) were used to evaluate apparent indicators. The levels of COR and ACTH in the serum, as well as the levels of 5-HT, NE, and BDNF in the hippocampus and medial prefrontal cortex were detected using ELISA to identify the physiological state. After acute stress, pigs exhibited decreased feed intake, decreased sucrose preference, increased serum COR levels, decreased hippocampal 5-HT levels, and fear. Finally, the model was evaluated according to the weight of the test indicators. The overall score of the model was 0.57, indicating modeling was feasible. Although the reliability and stability require further verification, this novel model revealed typical depression-like changes in behavior and provided a potential method to establish a model of depression in pigs.